Terror to the wicked : America's first trial by jury that ended a war and helped to form a nation - Pearl, Tobey (Pantheon Books, 2021)
"A brutal killing, an all-out manhunt, and a riveting account of the first murder trial in U.S. history--set in the 1600s in colonial New England against the backdrop of the Pequot War (between the Pequot tribe and the colonists of Massachusetts Bay), an explosive trial whose outcome changed the course of history, ended a two-year war, and brought about a peace that allowed the colonies to become a full-blown nation. The year: 1638. The setting: Providence, Plymouth Colony. A young Nipmuc tribesman, returning home from trading beaver pelts, is fatally stabbed in a robbery in the woods near Plymouth Colony, by a white runaway servant and fellow rogues. The young tribesman, fighting for his life, is able, with his final breaths, to reveal the details of the attack to Providence's governor, Roger Williams. A frantic manhunt by the fledgling government of Plymouth ensues, followed by the convening of the first trial, with Plymouth's governor Thomas Prence presiding as judge. The jury: local settlers (white) whose allegiance seems more likely to be with the accused than with the murdered (a native) . . . Tobey Pearl, piecing together a fascinating narrative through original research and first-rate detective work, re-creates in detail the full and startling, pivotal moment in pre-revolutionary America, as she examines the evolution of our nascent civil liberties and the role of the jury as a safeguard against injustice"--